The role of physico-chemical properties of liquid solder in reactive wetting: the Cu/SnZnIn system - Pstruś J. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The measurements of surface tension, density and viscosity of liquid Sn-Zn eutectic alloys containing 0, 5, 10, 15 and 25 mole fraction of In were carried out using the sessile drop method, dilatometric technique and capillary method. The measurements were performed at temperature range between 493 and 843 K. The technique of sessile drop was applied in the measurements of wetting angles and spreading test in the SnZnIn/ Cu system. Surface tension, density and viscosity measurements were carried out in a protective argon-hydrogen atmosphere. Wettability tests were performed in air in the presence of flux Alu33, at 250°C for 2 minutes. Subsequently, the microstructure of solder and the resulting joints was studied. The addition of In to eutectic Sn-Zn alloy improved the wetting properties and causes a reduction of thickness of the intermetallic compounds layer created at the interface between the liquid solder and the Cu substrate.